Heat Transfer Characteristics of an Aeroengine Turbine Casing Based on CFD and the Surrogate Model - Wenlei Lian; Yunfei Jiang; Hao Chen; Yi Li; Xianglei Liu (Energies, 2022)
A good turbine casing cooling design should control the thermal stress and maintain a reasonable tip clearance between the turbine blade and the casing. Since the turbine inlet temperature has been increased yearly, the influence of thermal radiation on the temperature of a turbine casing has become more significant. Therefore, the heat transfer characteristics of a turbine casing considering the radiation effect need to be precisely predicted. In this study, a theoretical model is established for describing the heat transfer characteristics of a turbofan casing, and the model’s effectiveness is verified by comparing the numerical and experimental results. Based on the validated model, the effects of single changes of the wall temperature, cooling air temperature, Reynolds number, and surface emissivity on the heat transfer of the casing are discussed. The results show that the increment of cooling air temperature and surface emissivity leads to the enhancement of the average radiative Nusselt number, and the average convective Nusselt number increases as the Reynolds number increases. The emissivity can improve the temperature distribution uniformity of the turbine casing. Finally, a Kriging surrogate model is fitted with 20 sample points to predict the joint effect of multiple parameters on the casing surface Nusselt number. It is found that the Reynolds number has a more significant influence on the average Nusselt number compared with the emissivity and the temperature ratio.